Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41467-019-14100-6
|View full text |Cite
|
Sign up to set email alerts
|

A network analysis to identify mediators of germline-driven differences in breast cancer prognosis

Abstract: Identifying the underlying genetic drivers of the heritability of breast cancer prognosis remains elusive. We adapt a network-based approach to handle underpowered complex datasets to provide new insights into the potential function of germline variants in breast cancer prognosis. This network-based analysis studies~7.3 million variants in 84,457 breast cancer patients in relation to breast cancer survival and confirms the results on 12,381 independent patients. Aggregating the prognostic effects of genetic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 80 publications
0
20
0
1
Order By: Relevance
“…Although several consortia have published on genetic variation that predicts survival in patients with breast cancer, no specific genetic markers have been identified that predict differences in survival metrics according to race. 13 - 16 There is limited evidence that genomic mutations in Chinese women with breast cancer differ significantly from those in White women, such as an increased prevalence of TP53 and AKT1 mutations, 4 which may translate into differences in oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although several consortia have published on genetic variation that predicts survival in patients with breast cancer, no specific genetic markers have been identified that predict differences in survival metrics according to race. 13 - 16 There is limited evidence that genomic mutations in Chinese women with breast cancer differ significantly from those in White women, such as an increased prevalence of TP53 and AKT1 mutations, 4 which may translate into differences in oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We took the SNPs referred to in Table 1 as genetic instruments for each of the nine risk factors. For every SNP, we performed survival analyses to obtain survival estimates as described previously [ 23 ]. The analyses included the full OncoArray and iCOGS datasets.…”
Section: Methodsmentioning
confidence: 99%
“…We also aimed to investigate whether we could observe—or refute—an effect for the risk factors for which the association is not clear. We therefore performed a two-sample MR analysis using genetic variants and risk factor association summary estimates from the GWAS Catalog [ 22 ] and breast cancer survival summary estimates from the Breast Cancer Association Consortium (BCAC) cohort [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Derived signatures can be validated in online (publicly) available datasets and in future studies. Genome-wide analysis of germ-line variations in almost 100,000 breast cancer patients in different cohorts revealed no major novel individual prognostic factors, whereas a network analysis identified the module 'cell growth and angiogenesis' to be prognostic for ER-but not ER+ breast cancer (101). One of the four components in this module was CHCHD4, which encodes a mitochondrial protein involved in HIF-1 stability and regulation of mitochondrial respiratory chain in tumor cell adaptation to hypoxia (33,102).…”
Section: Prognostic Markersmentioning
confidence: 99%